A separate peace - Knowles, John, 1926-2001. (New York : Scribner, 2003)
Set at a boys' boarding school in New England during the early years of World War II, A Separate Peace is a harrowing and luminous parable of the dark side of adolescence. Gene is a lonely, introverted intellectual. Phineas is a handsome, taunting, daredevil athlete. What happens between the two friends one summer, like the war itself, banishes the innocence of these boys and their world. A bestseller for more than thirty years, A Separate Peace is John Knowles's crowning achievement and an undisputed American classic.
Keywords: Preparatory school students -- Fiction; Friendship -- Fiction; Death -- Fiction; Boys -- Fiction; Preparatory schools -- Fiction; New Hampshire -- Fiction; Bildungsromans; Fiction; Bildungsromans